Kırsal kesimde görev yapan sınıf öğretmenlerinin fen bilimleri dersi öğretim sürecinde karşılaştıkları sorunlar. - SEYFİ, Rabia; DEMİRCİ GÜLER, Mutlu Pınar (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
The study aims to examine the problems encountered by primary school teachers working in rural areas of the Eastern Anatolia Region during the teaching process of science lessons. The research is quantitative designed and survey model. A sample of 205 primary school teachers was surveyed using a questionnaire consisting of 41 items and 5 dimensions, and 136 data sets suitable for evaluation were analysed using ANOVA and t-tests. The results of the study revealed that there was no significant difference in terms of gender, grade level taught, and class size in the dimensions of ‘problems encountered in pre-process preparation, problems encountered during the process, problems encountered in measurement and evaluation activities, problems encountered in relation to science lessons, and problems encountered in relation to the science lesson teaching programme’ included in the questionnaire. The mean value analysis revealed that class teachers encountered the most problems in the subdimension of ‘problems related to science lessons’ and the least in the sub-dimension of ‘problems encountered during the process’.